2016
DOI: 10.1161/strokeaha.115.012258
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Clinically Confirmed Stroke With Negative Diffusion-Weighted Imaging Magnetic Resonance Imaging: Longitudinal Study of Clinical Outcomes, Stroke Recurrence, and Systematic Review”

Abstract: We thank Reale et al 1 for their interest in our study, 2 and for describing their interesting case and suggestion that the absence of a diffusion-weighted imaging (DWI) lesion in a third of our patients with stroke was because of a shorter duration of ischemia.Disappearing DWI lesions are well documented to be associated with short duration and lesser severity of ischemic insult in animal models.3 Similarly, in patients, milder strokes are less likely to produce a DWI lesion than severe strokes. 4 Other facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 6 publications
3
79
1
1
Order By: Relevance
“…In fact, the mechanisms of END in patients with severe stroke or who are receiving thrombolytic therapy may differ from the mechanisms of END in the study population, as HT, brain edema, and other systemic conditions are likely to be more frequent in severe stroke patients than in mild stroke patients [13]. Third, despite the high sensitivity of DWI for ischemia detection, false negatives might occur in some locations, such as in small in- farcts or the brainstem [20,21]. A previous study reported that milder strokes are less likely to produce a DWI lesion than severe strokes [22].…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the mechanisms of END in patients with severe stroke or who are receiving thrombolytic therapy may differ from the mechanisms of END in the study population, as HT, brain edema, and other systemic conditions are likely to be more frequent in severe stroke patients than in mild stroke patients [13]. Third, despite the high sensitivity of DWI for ischemia detection, false negatives might occur in some locations, such as in small in- farcts or the brainstem [20,21]. A previous study reported that milder strokes are less likely to produce a DWI lesion than severe strokes [22].…”
Section: Discussionmentioning
confidence: 98%
“…Nearly one‐third of nondisabling stroke, especially those with small brain infarctions, those with infarctions in the posterior circulation or with infarctions causing mild perfusion deficits not amounting to induce diffusion‐weighted imaging (DWI) lesion are missed on the initial brain MRI, the so‐called MRI negative stroke (Makin, Doubal, Dennis, & Wardlaw, ; Saber Tehrani et al, ; Sylaja, Coutts, Krol, Hill, & Demchuk, ). We speculate that the absence of vertigo in patients with suspected vertebrobasilar stroke may be a warning sign for the presence of MRI negative stroke.…”
Section: Discussionmentioning
confidence: 99%
“…We also invited such patients who had participated in recent previous prospective studies. (20) All patients had a clinical stroke diagnosis confirmed by a specialist stroke physician and brain imaging that either confirmed a relevant recent infarct or, if no recent infarct was visible, excluded any other cause of the presenting symptoms. (20)…”
Section: Methodsmentioning
confidence: 99%